Efek Pemberian Enzim β-Mannanase pada Pakan Berbasis Soy Bean Meal Terhadap Nilai Kecernaan Energi, Kecernaan Protein dan Kadar Imunoglubulin Y Ayam Pedaging - laudita Setia Busta; Muhammad Halim Natsir; Eko Widodo (Faculty of Animal Science, Universitas Brawijaya, 2018)
Based poultry Indonesia feed formulation is corn soya, it is mean corn and soy bean meal has large proportion on the Indonesia poultry feed. The aims of the research to know the effects of β-mannanase enzyme as feed additive on soy bean meal based feed on the metabolizable energy, protein digestibility, and concentration immunoglobulin Y of broiler. This experiment used 20 broilers aged 35th days. Basal diet was comprised of corn, rice bran, fish meal, meat bone meal, stone lime, premix, coconout oil, methionine without β-mannanase enzyme (M0). Basal diet with β-mannanase enzyme 0.016% (M1), 0.033% (M2), 0.046% (M3). The variables measured were metabolizable energy, protein digestibility, and concentration immunoglobulin Y. The experimental designed in this experiment was completely randomized design with 4 treatments and 5 replications. The results show that the highest energy metabolizable is M3 3358.56±18.08c, highest protein digestibility is M3 81.01±0.70c, and highest concentration immunoglobulin Y is M3 5.09±3.21a. It can be concluded that β-mannanase enzyme in-crease of metabolizable energy, protein digestibility, and decrease concentration immunoglobulin Y of broiler.